Book art studio handbook : techniques and methods for binding books, creating albums, making boxes and enclosures, and more /: techniques and methods for binding books, creating albums, making boxes and enclosures, and more. ([2013]) - Dolin, Stacie; Lapidow, Amy
No abstract available